Quantitative Changes in the Publishing of Lithuanian Scientific Journals in 2015–2022: Public and Private Sectors’ Adaptation to the Changing Conditions - Petreikis, Tomas; Šuminas, Andrius; Grigas, Vincas; Gudinavičius, Arūnas (Knygotyra, 2024)
The article analyses the quantitative changes in the Lithuanian scientific journal publishing in 2015-2022. The study reveals the problems of public bibliographic accounting and terminology in order to comprehensively analyse the public and private sector published print and electronic scientific journals. The gaps and uncertainties identified allow for the improvement of official publication records in the future, avoiding ambiguities in the assessment of the publication volumes of scientific journals. Science policy makers and implementers should take the initiative to standardise the definition of scientific journals, as this is the only way to achieve a clearer approach to this form of science communication. Although the annual volume of scientific journal publications has shrunk by 18.1% (from 265 (2015) to 217 (2022) publications), the decline itself has not been sharp. The decline has been stabilised by business involvement, changes in the evaluation of colleges, and the transformation of professional journals, book series and conference proceedings into scientific journals. Flexibility has been provided by electronic publishing instruments, which have reduced the dependence on external financial sources. The public publishing sector has tended to reduce the number of scientific journals in all scientific fields. This was mainly due to the reorganisation of the higher education network, the qualitative requirements for scientific articles and the reorganisation of scientific collectives. The publishing business has seen the greatest potential in the fields of technology and the medical and health sciences, and as a result, the number of journals published in these fields has not declined and continues to grow. Despite the private sector's growth trends, 50% of journals have 30 or more years of publication. This forms the core of Lithuanian scientific journals, which public sector publishers are striving to preserve and integrate into the international scientific environment.
Keywords: scientific journals; science policy; periodicals publishing; bibliographic accounting; publishing statistics; terminology; Lithuania